1964
DOI: 10.1111/j.1151-2916.1964.tb14377.x
|View full text |Cite
|
Sign up to set email alerts
|

Glass Formation in Carbonate Systems

Abstract: YNTHESIS of a glass from the composition K2C02-MgCO3 was reported by Eitel and Skaliks' and since then no systematic S attempts to form carbonate glasses have been reported.The highly symmetrical co3 group is not expected to be easily distorted and consequently should not lend itself readily to glass formation. Limited areas of glass formation, however, have been found with certain carbonate compositions and with other selected compositions where volatile compounds must take part in network formation.at 1 kilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…-Synthesis of carbon nanoparticles in molten alkali carbonates for application in lithium-ion batteries [38]. -Use of some specific carbonate systems, such as K 2 CO 3 eMgCO 3 , where melts can be quenched to glasses [39]. -Role and properties of molten carbonate in geological applications [40].…”
Section: Miscellaneous Applications Of Molten Carbonatesmentioning
confidence: 99%
“…-Synthesis of carbon nanoparticles in molten alkali carbonates for application in lithium-ion batteries [38]. -Use of some specific carbonate systems, such as K 2 CO 3 eMgCO 3 , where melts can be quenched to glasses [39]. -Role and properties of molten carbonate in geological applications [40].…”
Section: Miscellaneous Applications Of Molten Carbonatesmentioning
confidence: 99%
“…The formation of a glass in the system K 2 CO 3 -MgCO 3 was, however, reported by Eitel and Skaliks as long ago as 1929 29 as a passing observation and has, with a few exceptions 30,31 received little attention. Glass in this system can be formed in a deep eutectic region at pressures of ~50 MPa 32,33 . The elevated pressure is believed to prevent the carbonate decomposing.…”
Section: Introductionmentioning
confidence: 98%
“…3). K 2 Mg(CO 3 ) 2 is unique among all carbonates in forming glass upon quenching 28 , which may explain the discrepancy in viscosity between K 2 Mg(CO 3 ) 2 and K 2 Ca(CO 3 ) 2 carbonate melts. Figure 5a shows a comparison of viscosities of carbonates (calcite and dolomite) melts determined in this study and those of basalt melts reported in a previous study 20 at high pressures.…”
Section: Article Nature Communications | Doi: 101038/ncomms6091mentioning
confidence: 99%
“…27. However, because K 2 Mg(CO 3 ) 2 has a structure distinct from other carbonate melts as evidenced by glass formation on quenching 28 , it likely does not represent typical carbonate melts. In addition, the frame rate employed for capturing images of the falling sphere during these experiments was insufficient to accurately define the terminal velocity, which is the basis for viscosity determination.…”
mentioning
confidence: 99%